2008
DOI: 10.1359/jbmr.080322
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Human Hydroxysteroid (17β) Dehydrogenase 2 Induces Disturbance in Skeletal Development in Young Male Mice

Abstract: ABSTRACT:To understand the function of human hydroxysteroid (17␤) dehydrogenase 2 (HSD17B2) in the peripheral tissues in vivo, we studied the bone development in transgenic male mice ubiquitously expressing human HSD17B2. Bones of HSD17B2TG and WT males (26 days and 2 and 6 mo old) were analyzed by pQCT and histomorphometry, and data were correlated with serum testosterone (T), IGF-I, and osteocalcin concentrations. At the age of 26 days, the body weight of HSD17B2TG males was significantly lower, and the leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Data on human bone outcomes and Pb are limited. However, Khalil et al (2008) reported that elevated BLLs are associated with an increased risk of falls and nonspine fractures, further validating this concern. Moreover, osteoporotic patients have a decreased capacity for healing of fractures.…”
Section: Discussionmentioning
confidence: 80%
“…Data on human bone outcomes and Pb are limited. However, Khalil et al (2008) reported that elevated BLLs are associated with an increased risk of falls and nonspine fractures, further validating this concern. Moreover, osteoporotic patients have a decreased capacity for healing of fractures.…”
Section: Discussionmentioning
confidence: 80%
“…Surprisingly, the HSD17B2TG mice did not show a significant rise in the tumor incidence which was expected according to the protective hypothesis for 17␤-HSD2. In a second study the same group showed that the over-expression of human 17␤-HSD2 led to disturbances in the skeletal development of male mice [124]. Studies with the HSD17B2TG suggested a sex-steroid independent role for 17␤-HSD2 besides its steroid converting function.…”
Section: ˇ-Hsd2mentioning
confidence: 98%
“…Studies with the HSD17B2TG suggested a sex-steroid independent role for 17␤-HSD2 besides its steroid converting function. To clarify this point a mouse bearing two genetic alterations was generated, ubiquitously expressing both human 17␤-HSD1 and human 17␤-HSD2 [124]. Using this "bi-TG mouse" the involvement of 17␤-HSD2 in sex steroid independent pathways could be proven.…”
Section: ˇ-Hsd2mentioning
confidence: 99%
“…Data in our recent studies applying TG mice expressing human HSD17B2 suggested that most marked physiological changes observed, such as growth retardation, delayed eye opening, and disrupted germ cell development, were not due to altered sex steroid action (24,33). The phenotypes observed together with the rescuing studies performed in male mice suggested that one putative explanation for the observed changes in the mice could be the alteration of retinoid and IGF action (33,34). Similarly, the phenotype of HSD17B2 knockout mice was not considered to be caused by altered estrogen or P action (25).…”
Section: Discussionmentioning
confidence: 96%